An MRI Study of Neurovascular Restorative After Combination Treatment With Xiaoshuan Enteric-Coated Capsule and Enriched Environment in Rats After Stroke - Zhan, Yu; Li, Man-Zhong; Yang, Le; Feng, Xue-Feng; Zhang, Qiu-Xia; Zhang, Nan; Zhao, Yuan-Yuan; Zhao, Hui (Frontiers in Neuroscience, 2019)
Xiaoshuan enteric-coated capsule (XSEC) is a Chinese medicinal compound widely used for treatment of ischemic cerebrovascular diseases. Enriched environment (EE) is an effective rehabilitative protocol designed to enhance sensorimotor, cognitive and social stimulation. This study aimed to apply magnetic resonance imaging (MRI) to noninvasively assess whether EE could augment the therapeutic benefits of XSEC on post-ischemic neurovascular remodeling. Male Sprague-Dawley rats were subjected to permanent middle cerebral artery occlusion (MCAO) and treated with XSEC and EE alone or combination for 30 consecutive days. Beam walking test and Morris water maze (MWM) test were performed to evaluate motor and cognitive function respectively. Multimodal MRI was applied to examine alterations to brain structures, intracranial vessels, and cerebral perfusion on the 31st day after MCAO. Double-immunofluorescent staining was used to evaluate neurogenesis and angiogenesis. Western blot and RT-PCR were used to detect the expressions of vascular endothelial growth factor (VEGF), angiopoietin-1 (Ang-1), angiopoietin-2 (Ang-2), and the axon guidance molecules. Combination therapy with XSEC and EE significantly reduced cystic volume compared with XSEC and EE monotherapies. In line with this, combination treated rats performed better in the beam walking test and exhibited improved spatial memory in the probe trial of the MWM. Moreover, XSEC and EE combination treatment improved cerebral blood flow (CBF), amplified angiogenesis and upregulated VEGF protein levels. This proangiogenic effect was consistent with the increased progenitor cell proliferation and neuronal differentiation in the peri-infarct cortex and striatum. Specifically, the combined therapy of XSEC and EE markedly increased the Netrin-1 and Robo-1 protein expression levels compared with vehicle group, while no difference was observed between XSEC or EE monotherapy and vehicle group. Together, these findings indicate that the combination of XSEC and EE benefits neurovascular reorganization. This correlates with restoration of CBF, promotion of neurogenesis and angiogenesis, and activation of the intrinsic axonal guidance molecules, thereby facilitating greater physical rehabilitation after ischemic stroke.